The inflence of TiO2 structure on the complete decomposition of acetaldehyde gas. (June 2020) - Tryba, B.; Rychtowski, P.; Srenscek-Nazzal, J.; Przepiorski, J.
Graphical abstract: Highlights: Adsorption of acetaldehyde on TiO2 depends mainly on its specific surface area. Acetaldehyde is physisorbed on the amorphous titania by carbonyl group. Dehydroxylation of TiO2 surface increase chemical mode adsorption of acetaldehyde. Physisorbed acetaldehyde on TiO2 surface does not follow photocatalytic decomposition. The structure of TiO2 with high pores size facilitates diffusion of byproducts. Abstract: Crystallisation of amorphous TiO2 have been performed by two steps, the hydrothermal method and following heating in Ar at 450 °C or mild heating at 200 °C under vacuum. Both methods were successful in reducing the amount of OH groups on TiO2 surface, however heating at high temperature caused significant decrease of BET surface area and increase in mesoporosity of TiO2 . Low hydroxylated surface of TiO2 caused, that acetaldehyde was adsorbed on its surface with chemical bounding and then could be decomposed via photocatalytic process. Although amount of acetaldehyde decomposed on TiO2 was comparable for both thermal heated samples, that than prepared at 200 °C under vacuum showed higher mineralisation degree and lower emission of formaldehyde from its surface. It appeared, that large pores present in sample heat treated at 450 °C favored diffusion of the formed byproducts from its surface and consequently lower mineralisation degree was obtained.